Therapeutic Communication in Forming Corporate Culture for Work Stress Management at PT. Astra Internasional - Rahma, Fadilah Annisa; ÔÇÿUyun, Zafirah Quroatun; Sanjaya, Andreas Ryan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The study aims to identify the role of therapeutic communication techniques in shaping a corporate culture that supports work stress management through a systematic literature review. As emphasized by Schein (2021), an effective organizational culture is built through communication patterns that are consistent with the company's core values. The study findings revealed that the implementation of therapeutic communication techniques - which include an empathetic approach, active listening, and supportive responses - in corporate culture can significantly reduce symptoms of work stress, including anxiety and burnout (Workplace Mental Health Institute, 2023). Organizations with an open communication culture that adopt therapeutic communication principles tend to have higher levels of employee resilience at PT. Astra (Gallup, 2022). As stated by Miller and Chen (2022), the integration of therapeutic communication techniques into daily management practices not only improves employee psychological well-being but also contributes to increased overall organizational productivity. This study provides several practical implications, including: (1) the importance of integrating therapeutic communication principles into internal communication policies, (2) the need for management training that focuses on developing empathetic communication skills, and (3) the design of employee well-being programs based on a therapeutic communication approach. This finding reinforces SHRM's (2022) view of the crucial role of communication culture in creating a healthy and productive work environment.